Inbred burying beetles suffer fitness costs from making poor decisions. Issue 1881 (27th June 2018) - Richardson, Jon; Comin, Pauline; Smiseth, Per T.
Abstract : There is growing interest in how environmental conditions, such as resource availability, can modify the severity of inbreeding depression. However, little is known about whether inbreeding depression is also associated with differences in individual decision-making. For example, decisions about how many offspring to produce are often based upon the prevailing environmental conditions, such as resource availability, and getting these decisions wrong may have important fitness consequences for both parents and offspring. We tested for effects of inbreeding on individual decision-making in the burying beetle Nicrophorus vespilloides, which uses the size of a carrion resource to make decisions about number of offspring. Both inbred and outbred females adjusted their initial decisions about number of eggs to lay based on carcass size. However, when we forced individuals to update this initial decision by providing them with a different-sized carcass partway through reproduction, inbred females failed to update their decision about how many larvae to cull. Consequently, inbred females reared too many larvae, resulting in negative fitness consequences in the form of smaller offspring and reduced female post-reproductive condition. Our study provides novel insights into the effects of inbreeding by showing that poor decision-making by inbred individuals can negatively affect fitness.